Mobile Application Profiling for Connected Mobile Devices - Díaz-Zayas, Almudena; Merino-Gómez, Pedro; Rivas Tocado, Francisco Javier (IEEE, 2010)
The SymPA (Symbian Protocol Analyzer) tool correlates traffic information, radio-access-technology measurements, and location data to help developers evaluate mobile applications in the field.
Keywords: Sistemas de comunicación inalámbricos; Teléfonos móviles; Mobile internet; Mobile networks; Performance; Mobile applications